OPTIMALISASI PEMBELAJARAN BAHASA ARAB DI MASA COVID-19 MELALUI E-LEARNING PADA PRODI NON BAHASA ARAB - Asdari, Adang; Nisa', Mauidlotun; Hady, Yazid; Kasyful Anwar, Abdul Wadud (Arabi : Journal of Arabic Studies, 2022)
This study aims to reveal the optimization of the use of E-Learning by lecturers and students in learning Arabic during the Covid 19 Pandemic. In addition, this study also shows how E-Learning provides a new face for learning models that can improve students' Arabic language skills even though they are studying in conditions without a face-to-face lecturer. This research is qualitative research with a political approach and educational psychology. This study found that Arabic language lecturers have used E-learning optimally, especially in responding to the Covid-19 pandemic. It refers to the finding that 52.7% of students stated that implementing E-Learning in Arabic learning was feasible, and even 14% stated it was very feasible. There are 45.7% of students interested in learning Arabic with E-Learning; even 14.7% said they were very interested. 49% of students stated that the material delivered by the lecturer using E-Learning was sufficient; even 10.1% stated it was sufficient. From the findings, it can be concluded that learning Arabic at UIN Jakarta during the Covid 19 pandemic has been going quite well by using E-Learning as optimally as possible.